2014
DOI: 10.1161/atvbaha.114.303217
|View full text |Cite
|
Sign up to set email alerts
|

Receptor Tyrosine Kinases Endocytosis in Endothelium

Abstract: Receptor tyrosine kinases (RTKs) are involved in regulation of key process in roles in endothelial biology including proliferation, migration and angiogenesis. It is now generally accepted that RTK signaling occurs intracellularly as well as on the plasma membrane although many important details remain to be worked out. Endocytosis and subsequent intracellular trafficking spatiotemporally regulate RTK signaling while “signaling endosomes” provide a platform for the compartmentalization of signaling events. Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 76 publications
0
15
0
Order By: Relevance
“…Interestingly, we did not see a significant change in FGFR1 protein expression, but did see a trend for reduced expression following extinction. FGFR1 is part of the tyrosine kinase receptor family (Johnson and Williams, 1993) and when bound by bFGF is trafficked to the nucleus (Myers et al, 2003;Zhang and Simons, 2014). Therefore, examining synaptic or nuclear expression instead of whole-cell expression may reveal a change in FGFR1 protein localization.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, we did not see a significant change in FGFR1 protein expression, but did see a trend for reduced expression following extinction. FGFR1 is part of the tyrosine kinase receptor family (Johnson and Williams, 1993) and when bound by bFGF is trafficked to the nucleus (Myers et al, 2003;Zhang and Simons, 2014). Therefore, examining synaptic or nuclear expression instead of whole-cell expression may reveal a change in FGFR1 protein localization.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, it has been shown that NRP1 acts as a coreceptor for VEGFR2. When VEGFR2 binds NRP1, it is recycled to the plasma membrane rather than trafficked to the lysosome for degradation (8,9,28). In light of these established findings, we hypothesized that ARF6 might affect VEGFR2 trafficking by influencing its interaction with NRP1.…”
Section: Gep100-arf6 Promotes Binding Of Vegfr2 With Its Coreceptor Nmentioning
confidence: 98%
“…New blood vessels are generated from the preexisting ones by a series of successive steps, including endothelial sprouting and tube formation. Typically, these processes are regulated by angiogenic factors, such as vascular endothelial growth factors, 13 fibroblast growth factors, 4, 5 and platelet derived growth factors. 6 In particular, VEGF-A induces tip cell formation leading to vascular ingrowth into avascular areas.…”
Section: Introductionmentioning
confidence: 99%